A contagion through exposure to foreign banks during the global financial crisis - Cyn-young Park; Kwanho Shin (Asian Development Bank (ADB), 2017)
Although the global financial crisis of 2008 took root in the advanced countries, its shocks spread through the emerging economies, reflecting the increasingly interconnected global financial system. This paper develops an empirical methodology to test the contagion effect at the country level using bilateral data on bank claims between countries. It measures the direct and indirect exposures of emerging economies to crisis countries and tests whether these matter for capital outflows from emerging economies. The paper measures these exposures to the crisis-affected countries by using bilateral foreign claims sourced from Bank for International Settlements (i) consolidated banking statistics foreign claims on immediate counterparty and ultimate risk bases and (ii) locational banking statistics cross-border total claims. Findings show that emerging market economies more exposed directly or indirectly to banks in the crisis-affected countries suffered more capital outflows during the global financial crisis.
Keywords: E44; F15; F21; F34; F38; F42; F62; 330; capital outflows; contagion; direct/indirect exposures; global financial crisis; interconnectedness